2010
DOI: 10.1007/s00393-010-0652-y
|View full text |Cite
|
Sign up to set email alerts
|

Conception and course of eight pregnancies in five women on TNF blocker etanercept treatment

Abstract: The introduction of tumor necrosis factor (TNF)-α inhibitors s in the late 1990s considerably broadened the treatment options for, and essentially contributed to the successful management of, rheumatoid arthritis (RA) and other immune-mediated inflammatory diseases. Nevertheless, their use during pregnancy is still controversially discussed since it remains unclear whether the benefits of treatment might be outweighed by potential teratogenicity or adverse effects on the course of pregnancy. In this case serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Nevertheless, their use during pregnancy is still controversial, because it remains unclear whether the benefits of treatment might be outweighed by potential teratogenicity or adverse effects on the course of pregnancy. Based on the available literature, experts suggest that continuation of treatment with TNF-α blockers is justified in pregnant patients with high disease activity and disease progression 9597…”
Section: Safety Of Etanercept In Asmentioning
confidence: 99%
“…Nevertheless, their use during pregnancy is still controversial, because it remains unclear whether the benefits of treatment might be outweighed by potential teratogenicity or adverse effects on the course of pregnancy. Based on the available literature, experts suggest that continuation of treatment with TNF-α blockers is justified in pregnant patients with high disease activity and disease progression 9597…”
Section: Safety Of Etanercept In Asmentioning
confidence: 99%
“…Several case series, case reports, and retrospective studies have concluded that adalimumab, etanercept, and infliximab have all been consistent with the old FDA categorization of pregnancy class B (Berthelot et al, 2009, Carter et al, 2006, Kane et al, 2009, Katz et al, 2004, Mahadevan et al, 2005, Mishkin et al, 2006, Murashima et al, 2009, Rump and Schönborn, 2010). This is all consistent with the 2012 NPF recommendations that these drugs should be regarded as third-line treatments for pregnant psoriasis patients (Bae et al, 2012).…”
mentioning
confidence: 76%